(untitled) (Global Journal of Management and Business Research, 2017)
Various studies have explored the concept of staff reward and recognition schemes and the effect they have on staff motivation and performance. Attention has also been given to how these programs contribute to the overall realization of organizational goals. This study was conducted to determine the effects of reward and recognition on employee job performance in Kenyatta University. Moreover, the relationship between other factors affecting performance (working environment and leadership styles) and performance was also explored with the help of responses collected from employees working in Kenyatta University main campus, Nairobi. A descriptive research design was used in the investigation of the effects of rewards and recognition on Kenyatta University staff performance. Stratified random sampling and purposive random sampling were used in sampling design.